Audiobook as a Medium for Conserving Sundanese Folklore and Enhancing the Language Skills of Generation Alpha - Agatha T Trisari; Langgeng Prima Anggradinata; Qotrunnadya Khusnul Wardati; Aesha Yusi Mahameru (DAWUH : Islamic Communication Journal, 2026)
The Sundanese language, despite being the second most widely spoken regional language in Indonesia, faces declining use among younger generations who perceive it as irrelevant. This study addresses how oral Sundanese folklore can be conserved and simultaneously transformed into an effective learning medium for Generation Alpha. Employing a research-and-development approach combined with a one-group pretest–posttest experimental design, the study conserved the folklore “Sejarah Sri Baduga Maharaja dan Batu Tulis” through the stages of data collection, validation, value analysis, and transformation into a bilingual illustrated audiobook. The cognitive theory of multimedia learning and the concept of literary transformation from orality to literacy frame the analysis. The product was tested on 27 fourth-grade students at SDIT Wadi Al Ahgaff, Bogor. Results shown significant improvement in Sundanese knowledge (30.00 to 98.41; t = 19.63; p < 0.001; N-Gain 0.98) and language skills (43.25 to 83.57; t = 30.23; p < 0.001; N-Gain 0.72), both with very large effect sizes. The study contributes a replicable model of folklore conservation that bridges cultural preservation and digital-era pedagogy, supporting SDG 4 on quality education.